Global Research on Nutraceutical Crops: Bibliometric Analysis and the Latent Potential of Agricultural Extension - Sekhri, Anukrati; RANAWAT, RAGINI; Jain, Harsha (Indian Journal of Extension Education, 2025)
Nutraceutical crops are gaining importance for their role in improving nutrition, supporting health, and promoting sustainable agriculture. Yet their impact depends on how effectively this knowledge is transferred to farmers through agricultural extension. This study analysed global research on nutraceuticals and agricultural extension using 3,485 Scopus-indexed publications between 2015 and 2024. Bibliometric tools (Biblioshiny and VOSviewer) were used to examine publication growth, authors, contributing countries, keyword patterns, thematic clusters, and collaboration networks. Analysis reveals steady progress over time, accelerating after 2020. India emerged as the clear global leader, followed by the USA and China, with institutional participation from universities such as Charles Sturt University and King Saud University. Research activity covered two areas: themes related to agriculture and sustainability, such as food security, climate change, and farming practices; and studies on plant-derived compounds including phytochemicals, antioxidants, and bioactive substances. The most important finding of this study is the near absence of extension-related themes. Although the search strategy included extension terms, they did not emerge as clusters or trends. This highlights a significant gap: while research on nutraceuticals is expanding rapidly, very little attention is given to how this knowledge is transferred to farmers.